Weizhia (Fabaceae: Phaseoleae), a new endemic genus from East China supported by morphological and molecular evidence - Jiang, Kai-Wen; Chen, Yue; Li, Hua-Dong; Ma, Dan-Dan; Pan, Bo; Song, Zhu-Qiu; Wan, Kai-Yuan; Chen, Zheng-Hai; Li, Gen-You (Phytotaxa, 2023)
Weizhia gen. nov. (Fabaceae) is here described as a new monotypic genus with the sole species W. pentaphylla sp. nov. from Zhejiang Province, East China. Both morphological and molecular phylogenetic evidence (nrITS + cpmatK) suggest that it is closely related to Dumasia and Toxicopueraria within the subtribe Glycininae (Fabaceae: Phaseoleae), but mainly differs by having usually pinnately 5-foliolate leaves and spurred wing-petals. A key to all genera of Glycininae currently recognized is also proposed. The new species is considered to be Critically Endangered according to IUCN categories and criteria, and in need of urgent protection.